Pearls & Oy-sters: Spinal Cord Candidiasis Linked to CARD9 Deficiency Masquerading as a Longitudinally Extensive Transverse Myelitis. (13th September 2022) - Jeantin, Lina; Plu, Isabelle; Amador, Maria del Mar; Maillart, Elisabeth; Lanternier, Fanny; Pourcher, Valérie; Davy, Vincent
Abstract : Candida spp. myelopathies are very rare. We report a case of subacute longitudinally extensive transverse myelitis in an apparently immunocompetent 55-year-old man. After a negative infectious workup, corticosteroids and plasma exchange were initiated. Although there was a transient initial improvement, symptoms then worsened, and the lumbar puncture was repeated. Candida albicans was isolated in the CSF, and a diagnosis of spinal cord candidiasis was made. Gene panel sequencing for inborn immune deficiencies identified a homozygous disease-causing CARD9 variant. Despite antifungal treatment, necrotic myelitis, meningoencephalitis, and cerebral vasculitis developed. Fungal spinal cord infections can mimic inflammatory myelitis, and beta-D-glucan testing of both serum and CSF may help narrow down the diagnosis. In cases of severe or unexpected invasive Candida spp. infection, even adults and apparently immunocompetent patients should be screened for inborn immune deficiencies and CARD9 deficiency in particular.